Closing the Education Gap : A Brief Overview of Programs for Low SES Students - Gilane, Deanna; Kerber, Anna; Eppolite, Mary; Blaskowski, Jay (My University, 2015)
In our research, we looked into programs and factors that helped students of low socioeconomic status achieve greater success in school. We looked at specific programs and services provided to students many of whom have low socioeconomic status both in and out of the school setting.What can we do to decrease the education gap between students of high socioeconomic status and low socioeconomic status?
Color poster with text and images.
Keywords: Education; Low income students; Posters